Sectoral productivity growth and poverty reduction: National and global impacts - Ivanic, Maros; Martin, Will (Elsevier, 2018)
This paper examines the implications of productivity improvements in agriculture, industry, and services for global poverty. We ﬁnd that, in poor countries, increases in agricultural productivity generally have a larger poverty-reduction effect than increases in industry or services. This differential declines as average incomes rise, partly because agriculture becomes smaller as a share of the economy, and partly because agricultural productivity growth becomes less effective in reducing poverty. The source of the poverty-reduction beneﬁts from agricultural productivity growth changes as innovations are more widely adopted—moving from increases in producer returns to reductions in consumer prices.